PENERAPAN ALIRAN PSIKOLOGI HUMANISTIK DALAM PROSES PEMBELAJARAN - Siti Mumun Muniroh (IAIN Pekalongan, 2011)
Abstract: Humanistic Psychology has the view that human behavioris driven by self-consciousness and purpose. Humanistic psychologybelieves that a person forming his own life because every person isthe free perpetrator and independent. That view affects significantlyfor the learning process threfore it impacts on the achievement ofeducational goals. As it is understood, that the ultimate purpose ofeducation is to discover and develop the nature of humanity. Themain mandate of education is ‘ humanizing’ human who experience‘dehumanization’ due to the unfair systems and structures, which inreality is not as simple as imagined. For that, they need speciallearning strategies derived from humanistic psychology